Hubungan Sistem Pendokumentasian Keperawatan Berbasis Elektronik dengan Kualitas Pelayanan Keperawatan di Unit Rawat Jalan Dua RSUD - Muhammad Azhar Faridzal; Maridi Marsan Dirdjo; Ulfatul Muflihah (Jurnal Sehat Mandiri, 2024)
Documentation is a process of activities that starts with examinations, formulation of diagnosis, action plans, nursing actions and evaluations that are recorded in electronic and manual form and are accountable. A quality nursing foster care documentation affects the quality of the care services and the reflection of the qualities of the nurse care. The aim of this research is to find out the relationship between the electronic nursing documentation system and the quality of nurses' services in RSUD's two-way care units. This type of research is a descriptive correlation using a cross sectional approach. Sampling was done using the total sampling method of 71 respondents. Data collection techniques using electronic nursing documentation research questionnaires and nurse performance. Data analysis using bi-variant analysis with correlation coefficient test of person product moment. The results of the study showed that the pearson analysis of the product moment obtained a r value of 0.744 which means that it has a strong relationship, showing a positive direction and with a p-value of 0,000 means that there is a significant relationship between the electronic nursing documentation system based on the quality of nursery services in the road nurseries unit two RSUD. Hospital management is expected to begin migration from conventional documentation to electronic documentation systems in both street care and hospital care to improve the quality of nursing services.